The European Slaughterhouse: Odense Theatre - Exe Christoffersen, Erik (Peripeti, 2023)
Script: William Shakespeare. Staging and adaptation: Tue Biering. Dramaturg: Mathias Rosenkrands Bech. Set and costume design: Nicolaj Spangaa and Marie Rosendahl Chemnitz. Composer: Daniel Fogh. Sound design: Kim Malmose. Lighting design: Simon Holmgren. Cast: Frank Thiel, Kristoffer Helmuth, Benjamin Kitter, Klaus T. Søndergaard, Freja Klint Sandberg, Natalí Vallespir Sand, Anders Gjellerup Koch, Nicolai Jandorf, Louise Davidsen, Malene Melsen, Mikkel Bay Mortensen, Githa Lehrmann, Niels Skovgaard Andersen, Cecilie Gerberg and others. https://iscene.dk/2022/09/01/tue-biering-det-er-er-mit-personlige-waterloo/